The Sculpture of Scientific Revolutions. Volume II, Number 2 - Thomas Samuel Kuhn (USA University of Chicago Press, 1973)
An analysis of the history of science. Its publication was a landmark event in the sociology of knowledge, and popularized the terms paradigm and paradigm shift
Introduction: A role for history -- The route to normal science -- The nature of normal science -- Normal science as puzzle-solving -- The priority of paradigms -- Anomaly and the emergence of scientific discoveries -- Crisis and the emergence of scientific theories -- The response to crisis -- The nature and necessity of scientific revolutions -- Revolutions as changes of world view -- The invisibility of revolutions -- The resolution of revolutions -- Progress through revolutions -- Postscript: 1969
Keywords: Natural Sciences (3GdYdhe GdHMJIs; Philosophy; Science; General